Efektivitas Penerapan Terapi Sosial Skills Training Terhadap Kemampuan Berinteraksi Pasien Dengan Isolasi Sosial Di Puskesmas Limboto - Adam, Sarita; Firmawati (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: : If social isolation is not addressed, there is a risk of other nursing problems arising such as the risk of sensory perception disorders, hallucinations, the risk of violent behavior, the risk of injuring oneself and others. Therefore, nursing action is needed to overcome the problems and risks that will arise. One therapy that can be used is Social Skill Training Therapy (SST). This research is to determine the effectiveness of implementing social therapy skills training on the interaction ability of patients with social isolation at the Limboto Community Health Center. Methods: used in this research was pre-experimental with a one-group pre-post test design approach, with a sample size of 15 respondents in this study. Results: Based on the results of statistical tests using the Wilcoxon test, a significant value or PV value was obtained, namely 0.001, which means 0.001<0.05, so it can be concluded that Ha is accepted, which means that the application of social therapy skills training is effective on the ability to interact with patients in social isolation at the Limboto Community Health Center. Conclusion: : It is hoped that this will provide additional information to health workers at the Limboto Community Health Center about providing social therapy skills training to patients experiencing social isolation.